Prepreg, molded body and integrated molded body

JP7639343B2Active Publication Date: 2025-03-05TORAY INDUSTRIES INC
View PDF 11 Cites 0 Cited by

Patent Information

Application Number
JP2020564012
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-12-23
Filing Date
2020-11-06
Publication Date
2025-03-05
Estimated Expiration
2040-11-06

AI Technical Summary

Benefits of technology

【0011】 本発明によれば、適度な柔軟性と粘着性を発現し、複雑な金型表面への賦形性と、金型表面への密着性に優れ、プリプレグの位置ズレが生じ難く、目的箇所へ効率良く補強·補剛することが可能なプリプレグを得ることができる。また、本発明のプリプレグが用いられた成形体および一体化成形体を得ることができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007639343000004
    Figure 0007639343000004
  • Figure 0007639343000005
    Figure 0007639343000005
  • Figure 0007639343000006
    Figure 0007639343000006
Patent Text Reader

Abstract

The present invention addresses the problem of providing: a prepreg which is heat-weldable to a member including a thermoplastic resin in injection molding or press molding, and in which, due to the loss tangent tan δ curve of a thermosetting resin having a specific peak measured by a dynamic viscoelasticity measurement method (DMA method), appropriate flexibility and adhesiveness are obtained, the prepreg has excellent formability to a complex die surface and adhesion to the die surface, there is no position shift of the prepreg, and the prepreg is capable of efficient reinforcement / stiffening in the desired location; and an integrally molded article, and the present invention relates mainly to a prepreg including (A) reinforcing fibers, (B) a thermosetting resin, and (C) a thermoplastic resin, the thermoplastic resin (C) being present on the surface of one side of a layer in which the reinforcing fibers (A) are impregnated with the thermosetting resin (B), and the loss tangent tan δ curve of the thermosetting resin (B) measured by a dynamic viscoelasticity measurement method (DMA method) having a peak in the range of 30-100°C inclusive.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a prepreg in which reinforcing fibers are impregnated with a thermosetting resin and a thermoplastic resin is present on at least a portion of the surface thereof. [Background technology]

[0002] Fiber-reinforced composite materials, which use a thermosetting resin as a matrix and combine it with reinforcing fibers such as carbon fiber and glass fiber, are lightweight yet have excellent mechanical properties such as strength and rigidity, heat resistance, and corrosion resistance, and have been applied to many fields such as aerospace, automobiles, railway vehicles, ships, civil engineering and construction, and sporting goods. However, these fiber-reinforced composite materials are not suitable for manufacturing parts and structures with complex shapes in a single molding process. In addition, in the above-mentioned applications, it is often necessary to prepare a member made of a fiber-reinforced composite material and then integrate it with the same or different members. As a method for integrating a fiber-reinforced composite material made of reinforcing fibers and a thermosetting resin with the same or different members, mechanical joining methods such as bolts, rivets, and screws, and joining methods using adhesives are used. In the mechanical joining method, a process of previously processing the joining parts such as drilling holes is required, which leads to a long manufacturing process and an increase in manufacturing costs, and there is also a problem that the strength of the material decreases due to drilling holes. Bonding methods that use adhesives require a bonding process that includes preparing the adhesive and applying the adhesive, as well as a curing process, which lengthens the manufacturing process time. This has led to problems with the adhesive strength and reliability not being fully satisfactory.

[0003] Here, Patent Document 1 discloses a method of bonding a fiber-reinforced composite material made of reinforcing fibers and a thermosetting resin via an adhesive. Patent Document 2 discloses a method of providing a thermoplastic resin on the surface of a fiber-reinforced composite material made of reinforcing fibers and a thermosetting resin, and integrating a member formed of the thermoplastic resin by injection molding. Patent Document 3 discloses a prepreg in which a polyolefin film is arranged on the surface of a layer made of carbon fibers and a semi-cured epoxy resin. Patent Document 4 discloses a prepreg in which particles, fibers, or a film made of a thermoplastic resin are arranged on the surface of a prepreg made of reinforcing fibers and a thermosetting resin, and a fiber-reinforced composite material thereof. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2018-161801 A [Patent Document 2] Japanese Patent Application Publication No. 10-138354 [Patent Document 3] Japanese Patent Application Publication No. 4-4107 [Patent Document 4] Japanese Patent Application Publication No. 8-259713 Summary of the Invention [Problem to be solved by the invention]

[0005] In Patent Document 1, fiber-reinforced composite materials made of reinforcing fibers and thermosetting resin are bonded together with an adhesive. Generally, in a method of bonding members together with an adhesive, it takes time for the adhesive to harden, and the bonding strength may also depend on the strength of the adhesive itself.

[0006] Patent Document 2 discloses a method in which a thermoplastic resin film is laminated on the surface of a prepreg made of reinforcing fibers and a thermosetting resin, the prepreg and the thermoplastic resin layer are integrated by heating and pressure curing to obtain a fiber-reinforced composite material, and then a member containing a thermoplastic resin is integrally molded by injection molding onto the thermoplastic resin layer on the surface of the fiber-reinforced composite material. However, since the thermosetting resin is cured, the fiber-reinforced composite material is rigid, and it is difficult to mold it into a mold having a complex surface shape. For this reason, it has been limited to application in a mold having a simple planar shape. In addition, since the thermosetting resin is cured, the fiber-reinforced composite material loses its surface adhesiveness, making it difficult to accurately position it in a mold, and it is difficult to efficiently reinforce and stiffen the desired location.

[0007] Patent Document 3 discloses a fiber-reinforced composite material in which a polyolefin film is laminated on the surface of a layer made of carbon fiber and semi-cured epoxy resin, and then the prepreg is cured in an autoclave, so that polyolefin film layers and carbon fiber / cured epoxy layers are laminated alternately. The purpose is to improve interlaminar fracture toughness by using a highly tough thermoplastic resin present between the layers, and is not intended to achieve thermal welding of the thermoplastic resin layer to other members, as in the prepreg of the present invention. In addition, there is no quantitative description of the degree of cure of the semi-cured epoxy, and no mention is made of selectivity depending on the degree of cure.

[0008] Patent Document 4 discloses a prepreg in which particles, fibers, or a film made of a thermoplastic resin are arranged on the surface of a prepreg made of reinforcing fibers and a thermosetting resin, and a fiber-reinforced composite material thereof. The purpose is to improve interlaminar fracture toughness by using a highly tough thermoplastic resin, as in Patent Document 3, and is not intended for thermal welding as in the prepreg of the present invention.

[0009] Thus, none of the prior arts have focused on the handleability of prepregs. Therefore, an object of the present invention is to provide a prepreg, a molded article, and an integrated molded article that exhibit appropriate flexibility and adhesion, have excellent formability to complex mold surfaces, and excellent adhesion to the mold surface, are free of prepreg positional deviation, and can efficiently reinforce and stiffen target locations. [Means for solving the problem]

[0010] The above-mentioned problems can be solved by a prepreg including (A) reinforcing fibers, (B) a thermosetting resin, and (C) a thermoplastic resin, in which the (B) thermosetting resin is impregnated into the (A) reinforcing fibers, the (C) thermoplastic resin is present on at least a portion of the surface of the prepreg, and the (B) thermosetting resin has a peak at 30°C or higher and 100°C or lower in a loss tangent tan δ curve measured by dynamic viscoelasticity measurement (DMA) method. Effect of the Invention

[0011] According to the present invention, it is possible to obtain a prepreg that exhibits appropriate flexibility and adhesion, has excellent formability to a complex mold surface, has excellent adhesion to the mold surface, is less likely to cause misalignment of the prepreg, and can efficiently reinforce and stiffen the target location. Also, it is possible to obtain a molded body and an integrated molded body using the prepreg of the present invention. [Brief description of the drawings]

[0012] [Figure 1] FIG. 1 is a schematic diagram (perspective view) of an example of a prepreg according to the present invention, in which a layer of (C) thermoplastic resin is provided on the entire surface of a layer in which (A) reinforcing fibers are impregnated with (B) thermosetting resin. [Diagram 2] FIG. 2 is a schematic cross-sectional view of an example of a prepreg according to the present invention. [Diagram 3] FIG. 2 is a schematic diagram for explaining a method for evaluating drapeability. [Figure 4]FIG. 1 is a schematic diagram of a loss angle δ curve measured for a region where (A) reinforcing fiber is impregnated with (B) thermosetting resin. [Diagram 5] FIG. 2 is a schematic diagram for explaining a procedure for producing a sample for evaluating bonding strength used in the Examples section. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0013] The present invention relates to a prepreg including (A) reinforcing fibers, (B) a thermosetting resin, and (C) a thermoplastic resin, in which the (B) thermosetting resin is impregnated into the (A) reinforcing fibers, and the (C) thermoplastic resin is present on at least a portion of the surface of the prepreg, and the (B) thermosetting resin has a peak at 30° C. or more and 100° C. or less in a loss tangent tan δ curve measured by a dynamic viscoelasticity measurement method (DMA method). and (A) reinforcing fibers that are present across the boundary between (B) a resin region containing a thermosetting resin and (C) a resin region containing a thermoplastic resin. .

[0014] The present invention will be described in detail below with reference to specific examples.

[0015] FIG. 1 shows an example of the prepreg of the present invention. In the prepreg shown in FIG. 1, the (B) thermosetting resin is impregnated into the (A) reinforcing fiber, and a layer of the (C) thermoplastic resin is provided on one surface of the sheet-shaped prepreg. The (C) thermoplastic resin has heat-welding properties, so that the (C) thermoplastic resin is present on the surface, and other members, particularly the member on the surface where the thermoplastic resin is present, can be welded and joined in a short time and well. Here, there is no particular restriction on the form in which the (C) thermoplastic resin is present, and it may cover the entire surface of the sheet-shaped prepreg or may cover only a part of it. It may also be in a form in which a plurality of regions are provided in an island shape. From the viewpoint of ensuring stable heat-welding properties, the proportion of the (C) thermoplastic resin present on the surface is preferably 50% or more, and more preferably 80% or more, when the area of ​​the prepreg surface on the side to which the (C) thermoplastic resin is applied is taken as 100%. In the drawing of FIG. 1, the (A) reinforcing fiber is drawn with a solid line to help understand the invention, but it actually exists in the prepreg. In addition, edges that are not actually visible when viewed from a squinting perspective are drawn with solid lines.

[0016] In addition, in the prepreg shown in Fig. 1, the thermoplastic resin (C) is not present on the surface opposite to the surface on which the thermoplastic resin (C) is present. That is, the surface is formed by a layer in which the reinforcing fiber (A) is impregnated with the thermosetting resin (B). By adopting such an embodiment, appropriate adhesion is exhibited at a general mold temperature (60 to 160°C) for injection molding or press molding, and positional deviation of the prepreg in the mold can be suppressed.

[0017] The (B) thermosetting resin constituting the prepreg of the present invention has a peak at 30° C. or more and 100° C. or less in the loss tangent tan δ curve measured by dynamic viscoelasticity measurement method (DMA method). In the present invention, the loss tangent tan δ curve of the (B) thermosetting resin measured by dynamic viscoelasticity measurement method (DMA method) is obtained by the following method. That is, i) If thermoplastic resin is present on the prepreg surface, remove it to prepare a piece of sample consisting of only thermosetting resin and reinforcing fiber. The sample weight should be about 1g.

[0018] ii) Using a dynamic viscoelasticity analyzer (ARES rheometer: manufactured by TA Instruments), the peak temperature of the tan δ curve is determined by constant speed heating measurement in accordance with JIS C6481. The peak temperature is plotted as a curve with temperature on the horizontal axis and tan δ, which is calculated as the ratio (G” / G') of the storage modulus G' and loss modulus G” of the prepreg on the vertical axis. The measurement conditions are as follows.

[0019] Heating rate: 5℃ / min Frequency: 1Hz.

[0020] By setting the peak temperature of the tan δ curve obtained from the relationship between temperature and tan δ to 30°C or higher, the adhesiveness of the thermosetting resin is suppressed, the handling becomes good, and the prepreg can be easily arranged in the mold for injection molding or press molding. On the other hand, if it is less than 30°C, the adhesiveness is expressed in a room temperature environment (23°C), so the handling becomes poor and it becomes difficult to arrange the prepreg in the mold for injection molding or press molding. In addition, by setting the peak temperature of the tan δ curve to 100°C or lower, moderate flexibility and adhesiveness are expressed at a general mold temperature (60 to 160°C) for injection molding or press molding, shaping to a complex mold surface is easy, and positional deviation of the prepreg in the mold can be suppressed. On the other hand, if it exceeds 100°C, moderate flexibility and adhesiveness are not expressed at a general mold surface temperature (60 to 160°C), shaping to a complex mold surface is difficult, and positional deviation occurs when arranging the prepreg in the mold. In other words, if the peak temperature of the tan δ curve of the thermosetting resin is outside the range of 30° C. to 100° C., it is not possible to efficiently reinforce and stiffen a member containing a thermoplastic resin using a prepreg and obtain an integrated molded product having excellent appearance characteristics. The peak temperature of the tan δ curve of the thermosetting resin is preferably in the range of 40° C. to 90° C., more preferably 50° C. to 80° C.

[0021] It is known that the peak temperature of the tan δ curve of a thermosetting resin depends on the degree of cure of the thermosetting resin. The degree of cure of the (B) thermosetting resin in the prepreg of the present invention is controlled to be within the range of the peak temperature of the tan δ curve, and for example, a method of adjusting the degree of cure to be within the range of the peak temperature of the tan δ curve described above by adjusting the cure temperature and time of the thermosetting resin can be exemplified.

[0022] In addition, the prepreg of the present invention preferably has (A) reinforcing fibers that exist across the boundary between the resin region containing (B) thermosetting resin and the resin region containing (C) thermoplastic resin, as shown in Fig. 2. Here, "(A) reinforcing fibers that exist across the boundary between the resin region containing (B) thermosetting resin and the resin region containing (C) thermoplastic resin" refers to (A) reinforcing fibers in a state in which both (B) thermosetting resin and (C) thermoplastic resin are in contact with each other all around at a certain portion of the fiber cross section, and / or in a state in which the entire circumference of a certain portion of the fiber cross section is in contact with the (B) thermosetting resin and the entire circumference of another portion of the fiber cross section is in contact with the (C) thermoplastic resin. By making such a prepreg, strong bonding strength can be obtained. In other words, since the (A) reinforcing fibers are present across both the resin region containing the (B) thermosetting resin and the resin region containing the (C) thermoplastic resin, the two resin regions are bonded via the (A) reinforcing fibers, thereby improving the bonding strength between the resin region containing the (B) thermosetting resin and the resin region containing the (C) thermoplastic resin.

[0023] Examples of methods for forming a state in which the (A) reinforcing fiber exists across the boundary between a resin region containing a (B) thermosetting resin and a resin region containing a (C) thermoplastic resin include a method in which the (A) reinforcing fiber is melted with a (C) thermoplastic resin to cover it from one side, and then the other side is impregnated with the (B) thermosetting resin, and a method in which the (A) reinforcing fiber is impregnated with a (B) thermosetting resin, and then the (C) thermoplastic resin is attached to the surface in the form of a sheet, nonwoven fabric, or particle, and then heated and pressurized at a temperature of the melting point +30°C or higher if the (C) thermoplastic resin is crystalline, or at a temperature of the glass transition temperature of the (B) thermosetting resin +30°C or higher if the (C) thermoplastic resin is amorphous, thereby causing both resins to flow at the boundary between the (B) thermosetting resin and the (C) thermoplastic resin to form the above state. When a resin with excellent resistance to moisture and heat is used as the (C) thermoplastic resin, the melting point of the thermoplastic resin is high, so the method of first covering one side with the (C) thermoplastic resin is preferable.

[0024] The prepreg of the present invention preferably has a drapeability, as defined below, of 3° or more. This allows for good shaping properties when placed in a mold having a complex shape with curved surfaces and corners for injection molding or press molding. The drapeability is more preferably 10° or more. There is no particular upper limit, but since a large degree of curvature can result in poor handleability, it is preferable to set the drapeability to 90° or less.

[0025] The drapeability in the present invention will be described below.

[0026] Drapability is an index that expresses the flexibility of a prepreg, that is, the ease of shaping into a mold. The measurement method is to cut out a sample with a width of 25 mm and a length of 300 mm to obtain an evaluation sample. At room temperature (23°C), as shown in Figure 3, 100 mm from the end of the sample is fixed to the top surface of a horizontal test stand with adhesive tape, and then further fixed with cellophane tape from above. The remaining 200 mm is arranged so that it protrudes into the air from the test stand, and the sample is held horizontally, and then the holding is released and it is allowed to hang down. 5 minutes after the holding of the sample is released, the tip of the sample bent by its own weight and the horizontal surface of the test stand are used as the drape angle to evaluate. At this time, the drape angle is expressed by the following formula, where the lowest point of the tip of the sample bent by its own weight is point a, the root protruding into the air is point b, and the intersection point when the sample is extended vertically from point a and horizontally from point b is point c. This measurement is carried out at five points, and the arithmetic average value is taken as the trape strength. Note that in Figure 3, the sample is deflected only at point b, but in actual samples, the sample usually draws an arc.

[0027] Drape angle θ(°) = {tan -1 (lac / lbc)}·(180 / π) Here, lac is the distance between points a and c, and lbc is the distance between points b and c.

[0028] It should be noted that the prepreg may have other components added to its surface, such as a release film, but it goes without saying that the prepreg is evaluated.

[0029] In the prepreg of the present invention, it is preferable that the region where the (A) reinforcing fiber is impregnated with the (B) thermosetting resin has a loss angle δ curve obtained by dynamic viscoelasticity measurement (DMA) defined below, the loss angle δ curve has a point showing a maximum value, and has a point on the short-time side of the point showing the maximum value where the loss angle δ is 5° or more smaller than the maximum value, i.e., has a peak with a height of 5° or more as viewed from the short-time side. In the present invention, the loss angle δ curve is obtained by the following method. That is, i) The thermoplastic resin present on the surface of the prepreg is removed, and a piece of sample consisting of only the thermosetting resin and reinforcing fibers is prepared. The sample is then laminated to a thickness of about 0.5 to 3 mm, typically about 1 mm. If the sample is a unidirectional material, it is laminated symmetrically.

[0030] ii) Using a dynamic viscoelasticity analyzer (ARES rheometer: manufactured by TA Instruments), measurements are taken under isothermal conditions in accordance with JIS K7244-10. The loss angle δ (°) is calculated using the elapsed time on the horizontal axis and the storage modulus G' and loss modulus G" of the prepreg on the vertical axis, and is expressed as tan -1 Place (G” / G') and draw a curve. The measurement conditions are as follows. Measurement is performed at the following three measurement temperatures, and any one of the obtained loss angle δ curves may satisfy the conditions of the preferred loss angle δ curve described above or later. The mold temperature used during molding should be selected at a temperature that satisfies this condition or a temperature close to it. Incidentally, the thermosetting resin used in the examples can be integrally molded at an injection mold temperature of 80°C, so the results shown are obtained at a measurement temperature of 80°C. A lower mold temperature is more preferable in terms of energy efficiency, so a prepreg that gives the preferred loss angle δ curve described above or later at a measurement temperature of 80°C is preferable.

[0031] Heating rate: 5℃ / min Starting speed: 30℃ Measurement temperature: 80℃, 110℃, or 140℃ Frequency: 10Hz.

[0032] In the loss angle δ curve, by having one peak with a height of 5° or more from the short-time side, i.e., the amount of change in the positive loss angle, the prepreg exhibits moderate flexibility and adhesion at the surface temperature of a general mold (60 to 160°C), and therefore can be easily shaped even on a mold curved surface with a small radius of curvature. In addition, in molding using a horizontal injection molding device, the prepreg can be easily attached to a vertical mold surface, so that integral molding is possible without positional deviation due to the influence of vibration when closing the mold or pressure when filling the resin. The shape of the loss angle δ curve with a peak includes the shape (shape 1) shown in FIG. 4(a) in which the maximum point appears from a region 17 with a gentle slope and no undulations, and the shape (shape 2) shown in FIG. 4(b) in which the maximum point appears from a curve with a positive slope, and among them, shape 2 in which the peak appears in a short time is more preferable. As a result, the prepreg surface does not have adhesion in a room temperature environment (23°C), and therefore the handling is even more excellent.

[0033] In the prepreg of the present invention, it is also preferable that the region where the reinforcing fiber (A) is impregnated with the thermosetting resin (B) does not have a peak with a height of 5° or more from the time side in the loss angle δ curve obtained by the dynamic viscoelasticity measurement method (DMA method) described above, as shown in FIG. 4(c), which has no peak. This makes it easy to handle in a room temperature environment (23°C), and it exhibits flexibility and adhesion at the surface temperature of a general mold (60 to 160°C), so it can be shaped into a flat plate or a mold curved surface with a large radius of curvature. In particular, it has excellent shape retention that can withstand high pressure during high-pressure molding of a large area.

[0034] That is, a prepreg having a peak with a height of 5° or more as viewed from the short-time side in a loss angle δ curve is suitably used for a mold curved surface with a small radius of curvature, and a prepreg without a peak is suitably used for a flat plate or a mold curved surface with a large radius of curvature.

[0035] The prepreg of the present invention preferably has an average thickness of the entire prepreg of 50 μm or more and 400 μm or less, and when the average thickness is taken as 100%, the average thickness of the resin region containing (C) thermoplastic resin is 2% or more and 55% or less. By setting the ratio of the average thickness of the resin region containing (C) thermoplastic resin to the average thickness of the entire prepreg within the above range, the drapeability is improved and shaping into a mold is facilitated. This ratio is more preferably 5% or more and 30% or less, and by setting it within this range, a prepreg having excellent shapeability, windability, and unwindability can be obtained. The average thickness of the entire prepreg and the average thickness of the resin region containing (C) thermoplastic resin can be measured as follows by observing the cross section of the prepreg using an optical microscope.

[0036] That is, a sample of 20 mm length x 25 mm width was taken from the prepreg, and the thickness of each part was measured as follows. The cross section of the sample was magnified 200 times with a laser microscope (Keyence Corporation, VK-9510), and images were taken at 10 randomly selected locations that did not overlap each other (for example, as observed in FIG. 2). In each image taken, 10 measurement positions were determined at equal intervals, and the thickness of the entire prepreg and the thickness of the thermoplastic resin were measured. The average values ​​of the measurement data for a total of 100 points were calculated as the average thickness T of the representative entire prepreg and the average thickness Tp of the resin region containing the thermoplastic resin. The difference between them was taken as the average thickness Ts of the thermosetting resin.

[0037] In the prepreg of the present invention, the (A) reinforcing fiber has a surface free energy measured by the Wilhelmy method of 10 m to 50 mJ / m 2 It is preferable to use a material having a reinforcing fiber strength of 10 to 40 mJ / m. This allows the reinforcing fiber (A) to exhibit high affinity with the thermosetting resin (B) and the thermoplastic resin (C), and allows the reinforcing fiber (A) to exhibit high bonding strength at the bonding interface between the thermosetting resin (B) and the thermoplastic resin (C) that are straddled by the reinforcing fiber (A). 2, more preferably 20 to 40 mJ / m 2 10mJ / m 2 If it is less than 50 mJ / m, the affinity between the (A) reinforcing fiber and the (B) thermosetting resin or (C) thermoplastic resin will be low, which will be disadvantageous in terms of bonding strength. 2 If it exceeds this value, (A) the reinforcing fibers will aggregate together, resulting in poor dispersion in the molded product and large variations in bonding strength.

[0038] (A) Methods for controlling the surface free energy of the reinforcing fiber surface include a method of controlling the surface by oxidizing the surface and adjusting the amount of oxygen-containing functional groups such as carboxyl groups and hydroxyl groups, and a method of controlling the surface by attaching a single compound or multiple compounds to the surface. When multiple compounds are attached to the surface, compounds with high and low surface free energy may be mixed and attached. Next, a method for calculating the surface free energy of the reinforcing fiber will be described.

[0039] The above-mentioned surface free energy can be calculated by measuring the contact angles of the (A) reinforcing fiber with three types of solvents (purified water, ethylene glycol, and tricresyl phosphate) and then using Owens' approximation formula. The procedure is as follows:

[0040] <Contact angle measurement> i) Using a contact angle meter (DCAT11: manufactured by DataPhysics), first, (A) one single fiber is taken from the bundle of reinforcing fibers and cut into eight pieces with a length of 12±2 mm. The single fibers are then attached in parallel to a dedicated holder FH12 (a flat plate with a surface coated with an adhesive substance) with 2-3 mm spacing between each fiber.

[0041] ii) The tips of the single fibers are trimmed and set in the contact angle meter on the holder. For the measurement, the cell containing each solvent is brought close to the bottom ends of the eight single fibers at a speed of 0.2 mm / s, and the single fibers are immersed up to 5 mm from the tips. The single fibers are then pulled up at a speed of 0.2 mm / s, and this operation is repeated four or more times.

[0042] iii) The force F acting on the single fiber while it is immersed in the liquid is measured using an electronic balance, and this value is used to calculate the contact angle θ using the following formula.

[0043] COSθ = (force F (mN) acting on 8 single fibers) / ((8 (number of single fibers) × circumference of single fiber (m) × surface tension of solvent (mJ / m 2 )) The measurements were carried out on single fibers extracted from three different locations of the reinforcing fiber bundle, that is, the average contact angle was calculated for a total of 24 single fibers for one reinforcing fiber bundle.

[0044] <Calculation of surface free energy> Surface free energy of reinforcing fiber γ f is the polar component of the surface free energy γ p f , and the non-polar component of the surface free energy γ d f The polar component of the surface free energy is calculated as the sum of the following Owens approximation formula (an equation composed of the polar and non-polar components of the surface tension specific to each solvent, and the contact angle θ), and after substituting the surface tension components and contact angle of each liquid into the formula, plotting it on X and Y, it can be calculated by squaring the slope a when approximating the line by the least squares method. Y = a X + b X = √(polar component of the surface tension of the solvent (mJ / m 2 )) / √(non-polar component of the solvent's surface tension (mJ / m 2 ) Y = (1 + COSθ) (polar component of the surface tension of the solvent (mJ / m 2 )) / (2×√(non-polar component of the solvent's surface tension (mJ / m 2 )) Gamma p f =a 2 Gamma d f =b 2 Gamma f =γ p f +γ d f =a 2+b 2 .

[0045] The polar and non-polar components of the surface tension for each solvent are as follows: ·Purified water Surface tension 72.8mJ / m 2 , polar component 51.0mJ / m 2 , non-polar component 21.8 (mJ / m 2 ) Ethylene glycol Surface tension 48.0mJ / m 2 , polar component 19.0mJ / m 2 , non-polar component 29.0 (mJ / m 2 ) Tricresol phosphate Surface tension 40.9mJ / m 2 , polar component 1.7mJ / m 2 , non-polar component 39.2 (mJ / m 2 ).

[0046] In the prepreg of the present invention, the (A) reinforcing fibers are preferably aligned in one direction. By aligning the (A) reinforcing fibers in one direction, the portion containing the thermoplastic resin can be efficiently reinforced and stiffened.

[0047] The prepreg of the present invention preferably has a tensile strength (tensile strength perpendicular to the fibers) of 0.3 MPa or more in a direction perpendicular to the arrangement direction of the (A) reinforcing fibers and parallel to the sheet surface. By setting the tensile strength within this range, fiber disorder due to injection pressure and press pressure can be suppressed when injection molding or press molding is adopted as a method for laminating or joining thermoplastic resin members in a later process. The tensile strength is more preferably 1.2 MPa or more, and by setting the tensile strength within this range, the prepreg can withstand the injection pressure during injection molding, which generates high pressure, especially with the fluidity of the resin. There is no particular upper limit, and the higher the better, but it is preferably about 1.5 MPa.

[0048] The tensile strength in the direction perpendicular to the fibers is measured by the method described below. (A) A prepreg in which reinforcing fibers are arranged in one direction is cut into a width of 50 mm and a length of 150 mm with the direction perpendicular to the fibers as the longitudinal direction to be used as an evaluation sample. The evaluation sample is set in a tabletop precision universal testing machine (Autograph AGS: manufactured by Shimadzu Corporation) so that the distance between the gripping jigs is 100 mm, and a tensile test is performed at room temperature (23°C) at a speed of 100 mm / min. The maximum load until the sample breaks is Pmax, and the horizontal cross-sectional area perpendicular to the longitudinal direction of the sample is A, and the tensile strength (MPa) in the direction perpendicular to the fibers can be calculated from the following formula. The number of evaluation samples is 5 or more, and the arithmetic average value is used. The tensile strength is the value obtained as the yield stress during the tensile test.

[0049] Tensile strength perpendicular to the grain (MPa) = Pmax / A.

[0050] The molded article of the present invention is a molded article obtained by heat-curing the above-mentioned prepreg on a mold. The molded article, which is heat-cured on a mold so as to have the same shape as the desired reinforcement / stiffening portion of an existing part, does not peel off from the surface of the existing part and exhibits an excellent reinforcing / stiffening effect. In particular, it is a molded article that can efficiently reinforce / stiffen large parts that are difficult to reinsert into the mold. The peak temperature of the tan δ curve of the obtained molded article is 100°C or higher.

[0051] The integrally molded article of the present invention is a molded article obtained by integrating the prepreg with a thermoplastic resin by injection molding or press molding. By using the prepreg, it is possible to efficiently reinforce or stiffen the desired portion of a thermoplastic resin member.

[0052] Next, each of (A) reinforcing fibers, (B) thermosetting resins, and (C) thermoplastic resins that can be suitably used in the present invention will be described.

[0053] <(A) Reinforced fiber> (A) Examples of reinforcing fibers include carbon fibers, glass fibers, metal fibers, aromatic polyamide fibers, polyaramid fibers, alumina fibers, silicon carbide fibers, boron fibers, and basalt fibers. These may be used alone or in combination of two or more. These reinforcing fibers may be surface-treated. Examples of surface treatments include metal deposition treatment, treatment with a coupling agent, treatment with a sizing agent, and additive attachment treatment. These reinforcing fibers also include conductive reinforcing fibers. As the reinforcing fibers, carbon fibers are preferably used because of their low specific gravity, high strength, and high elastic modulus.

[0054] In FIG. 1, the (A) reinforcing fibers are arranged in one direction. However, there are no particular limitations on the form of the reinforcing fibers as long as the reinforcing effect can be obtained. The reinforcing fibers may be continuous fibers such as long fibers (fiber bundles) aligned in one direction or woven fabric, or discontinuous fibers such as mats or nonwoven fabrics.

[0055] Furthermore, the (A) reinforcing fiber may be composed of a plurality of fibers of the same form, or may be composed of a plurality of fibers of different forms. The number of single filaments of the reinforcing fiber constituting one reinforcing fiber bundle is usually 300 to 60,000, but in consideration of the production of the base material, it is preferably 300 to 48,000, and more preferably 1,000 to 24,000. It may be within a range that is a combination of any of the above upper limits and any of the above lower limits.

[0056] Commercially available carbon fibers include "TORAYCA (registered trademark)" T800G-24K, "TORAYCA (registered trademark)" T800S-24K, "TORAYCA (registered trademark)" T700G-24K, "TORAYCA (registered trademark)" T700S-24K, "TORAYCA (registered trademark)" T300-3K, and "TORAYCA (registered trademark)" T1100G-24K (all manufactured by Toray Industries, Inc.).

[0057] <(B) Thermosetting resin> (B) Examples of the thermosetting resin include unsaturated polyester resin, vinyl ester resin, epoxy resin, phenol resin, urea resin, melamine resin, polyimide resin, cyanate ester resin, bismaleimide resin, benzoxazine resin, copolymers, modified products thereof, and resins obtained by blending at least two of these. In order to improve impact resistance, an elastomer or rubber component may be added to the thermosetting resin. Among them, epoxy resin is preferable because it has excellent mechanical properties, heat resistance, and adhesion to reinforcing fibers. Examples of the main component of the epoxy resin include bisphenol type epoxy resins such as bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AD ​​type epoxy resin, and bisphenol S type epoxy resin, brominated epoxy resins such as tetrabromobisphenol A diglycidyl ether, epoxy resins having a biphenyl skeleton, epoxy resins having a naphthalene skeleton, epoxy resins having a dicyclopentadiene skeleton, novolac type epoxy resins such as phenol novolac type epoxy resin and cresol novolac type epoxy resin, N,N,O-triglycidyl-m-aminophenol, and the like. Examples of the epoxy resins include glycidyl amine type epoxy resins such as phenol, N,N,O-triglycidyl-p-aminophenol, N,N,O-triglycidyl-4-amino-3-methylphenol, N,N,N',N'-tetraglycidyl-4,4'-methylenedianiline, N,N,N',N'-tetraglycidyl-2,2'-diethyl-4,4'-methylenedianiline, N,N,N',N'-tetraglycidyl-m-xylylenediamine, N,N-diglycidylaniline, and N,N-diglycidyl-o-toluidine, resorcinol diglycidyl ether, and triglycidyl isocyanurate.

[0058] Examples of the curing agent for the epoxy resin include dicyandiamide, aromatic urea compounds, aromatic amine compounds, phenol novolac resins, cresol novolac resins, polyphenol compounds, imidazole derivatives, tetramethylguanidine, thiourea-added amines, carboxylic acid hydrazides, carboxylic acid amides, and polymercaptans.

[0059] <(C) Thermoplastic resin> (C) Thermoplastic resin is not particularly limited as long as it is a resin that can be melted by heating, and examples thereof include polyester-based resins such as polyethylene terephthalate, polybutylene terephthalate, polytrimethylene terephthalate, polyethylene naphthalate, and liquid crystal polyester, polyolefins such as polyethylene, polypropylene, and polybutylene, styrene-based resins, urethane resins, polyoxymethylene, polyamides such as polyamide 6 and polyamide 66, polycarbonates, polymethyl methacrylates, polyvinyl chloride, polyphenylene sulfide, polyphenylene ether, modified polyphenylene ether, polyimides, polyamideimides, polyetherimides, polysulfones, modified polysulfones, polyethersulfones, polyarylene ether ketones such as polyketones, polyether ketones, polyether ether ketones, and polyether ketone ketones, polyarylates, polyether nitriles, phenolic resins, and phenoxy resins. These thermoplastic resins may be copolymers or modified bodies of the above-mentioned resins, or may be blends of two or more types selected from the above-mentioned resins and their copolymers and modified bodies. Among these, from the viewpoint of heat resistance, it is preferable to use a resin or resin composition in which one or more selected from polyarylene ether ketone, polyphenylene sulfide, or polyetherimide are contained in the thermoplastic resin (C) at 60% by weight or more. In order to improve impact resistance, an elastomer or rubber component may be added. Furthermore, depending on the application, etc., other fillers and additives may be appropriately contained within a range that does not impair the object of the present invention. For example, inorganic fillers, flame retardants, conductive agents, crystal nucleating agents, ultraviolet absorbers, antioxidants, vibration dampers, antibacterial agents, insect repellents, deodorants, coloring inhibitors, heat stabilizers, mold release agents, antistatic agents, plasticizers, lubricants, colorants, pigments, dyes, foaming agents, foam control agents, coupling agents, etc. may be mentioned.

[0060] In addition, when the thermoplastic resin (C) is applied to the sheet-like material in which the reinforcing fibers (A) are previously impregnated with the thermosetting resin (B), various application forms can be adopted. For example, the thermoplastic resin (C) is molded into a sheet or nonwoven fabric and laminated, or particulate thermoplastic resin (C) is sprayed onto the sheet-like material and integrated by applying heat.

[0061] <Application> The integrally molded article of the present invention can be obtained by placing the prepreg in a mold for injection molding or press molding and integrating it with a member containing a thermoplastic resin by insert molding. The integrally molded article of the present invention is preferably used for computer applications such as aircraft structural members, windmill blades, automobile outer panels and seats, IC trays and notebook computer housings, and sports applications such as golf shafts and tennis rackets. EXAMPLES

[0062] The present invention will be described in more detail below with reference to examples, but the scope of the present invention should not be construed as being limited to these examples.

[0063] (1) Materials used (A) Reinforced fiber A-1: Carbon fiber (TORAYCA (registered trademark) T700S-24K, manufactured by Toray Industries, Inc., strand tensile strength: 4.9 GPa). A-2: Carbon fiber (weight 193g / m 2 ) is a plain woven fabric.

[0064] Hereinafter, reinforcing fibers having various compounds described in A-3 to A-8 on the surface thereof will be described. These were obtained by obtaining a common carbon fiber bundle as a raw material by the following method, and then coating various compounds described in A-3 to A-8 below. That is, first, an acrylonitrile copolymer copolymerized with itaconic acid was spun and sintered to obtain a fiber having a total filament count of 24,000 and a specific gravity of 1.8 g / cm. 3A carbon fiber bundle having a strand tensile strength of 4.9 GPa and a strand tensile modulus of elasticity of 230 GPa was obtained. Then, each compound was mixed with acetone to obtain a solution of about 1 mass % in which the compound was uniformly dissolved. Each compound was applied to the carbon fiber bundle by immersion, and then heat-treated at 210°C for 90 seconds, and the amount of each compound attached was adjusted to 0.5 parts by mass per 100 parts by mass of the carbon fiber to which each compound was attached. A-3: Carbon fiber to which polyethylene glycol diglycidyl ether (ethylene oxide number 13, manufactured by Nagase ChemteX Corporation) was applied Surface free energy: 20mJ / m 2 A-4: Carbon fiber with bisphenol A propylene oxide 24 mole adduct Surface free energy: 18mJ / m 2 A-5: Carbon fiber with sorbitol polyglycidyl ether (EX614B, Nagase ChemteX Corporation) Surface free energy: 32mJ / m 2 A-6: Carbon fiber with polyallylamine (PAA-01, Nippon Shokubai Co., Ltd.) Surface free energy: 32mJ / m 2 A-7: Polyethyleneimine (SP-012, Nippon Shokubai Co., Ltd.) Surface free energy: 33mJ / m 2 Carbon fiber with A-8: Carbon fiber with bisphenol A diglycidyl ether (jER828, manufactured by Mitsubishi Chemical Corporation) Surface free energy: 9mJ / m 2 A-9: A plain weave of A-5.

[0065] Surface free energy: 32mJ / m 2 (B) Thermosetting resin It was prepared using the following ingredients: Epoxy resin base: "jER (registered trademark)" 828, 1001, 154 (all manufactured by Mitsubishi Chemical Corporation). Epoxy resin hardener: DICY7 (dicyandiamide, manufactured by Mitsubishi Chemical Corporation), "Omicure (registered trademark)" 24 (manufactured by PTI Japan Co., Ltd.), 3,3'DAS (3,3'-diaminodiphenyl sulfone, manufactured by Mitsui Chemicals Fine Co., Ltd.).

[0066] Using the above materials, thermosetting resins B-1 and B-2 were prepared according to the following method. B-1: 300g, 400g, and 300g of jER828, jER1001, and jER154 were placed in a stainless steel beaker, heated to 150°C, and kneaded until each component was compatible. After lowering the temperature to 60°C, 54g of DICY7T and 20g of Omicure24 were added, and kneaded at 60°C for 30 minutes to obtain thermosetting resin B-1. B-2: 300g, 400g, and 300g of jER828, jER1001, and jER154 were placed in a stainless steel beaker, heated to 150°C, and kneaded until each component was compatible. After lowering the temperature to 80°C, 260g of 3,3'DAS was added, and kneaded at 80°C for 30 minutes to obtain thermosetting resin B-2. (C) Thermoplastic resin C-1: Polyamide 6 ("Amilan" (registered trademark) CM1007 (manufactured by Toray Industries, Inc., melting point 225°C)) with a basis weight of 10 g / m 2 The film used was C-2: Polyamide 6 ("Amilan" (registered trademark) CM1007 (manufactured by Toray Industries, Inc., melting point 225°C)) with a basis weight of 30 g / m 2 The film used was C-3: Polyamide 6 ("Amilan" (registered trademark) CM1007 (manufactured by Toray Industries, Inc., melting point 225°C)) with a basis weight of 85 g / m 2 The film used was C-4: Acid-modified polypropylene ("Admer" (registered trademark) QB510 (Mitsui Chemicals, Inc., melting point 165°C)) with a basis weight of 30 g / m 2 The film used was C-5: Polyetherketoneketone ("KEPSTAN" (registered trademark) 7002 (manufactured by Arkema, melting point 331°C)) with a basis weight of 30 g / m 2 The film used was (D) Injection molding material D-1: 80 parts of polyamide 6 and 20 parts of the T700S were put into a twin-screw extruder and mixed at 250°C to obtain pellets for injection molding. The average fiber length of the T700S in the pellets was 0.1 mm. D-2: 80 parts of acid-modified polypropylene and 20 parts of the T700S were put into a twin-screw extruder and mixed at 250°C to obtain pellets for injection molding. The average fiber length of the T700S in the pellets was 0.1 mm. D-3: 80 parts of polyetherketoneketone and 20 parts of the T700S were put into a twin-screw extruder and mixed at 360°C to obtain pellets for injection molding. The average fiber length of the T700S in the pellets was 0.1 mm. (E) Thermoplastic plate material E-1: A randomly oriented fiber-reinforced thermoplastic resin consisting of 80 parts of polyamide 6 and 20 parts of the T700S was used. The plate thickness was 5 mm. E-2: A randomly oriented fiber-reinforced thermoplastic resin consisting of 80 parts of acid-modified polypropylene and 20 parts of the T700S was used. The plate thickness was 5 mm. E-3: A randomly oriented fiber-reinforced thermoplastic resin consisting of 80 parts of polyetherketoneketone and 20 parts of the T700S was used. The plate thickness was 5 mm.

[0067] (2) Prepreg manufacturing method The method for producing the prepreg used in this embodiment is described below.

[0068] [Method I] (A) Reinforced fiber (described in each Example and Comparative Example section; the same applies to Methods II and III) with a basis weight of 193 g / m 2The reinforcing fiber sheet was pulled out, and while the reinforcing fiber sheet was running, a film of a specified (C) thermoplastic resin (described in each Example and Comparative Example; similar to Methods II and III) was placed on the continuous reinforcing fiber sheet, heated with an IR heater to melt the (C) thermoplastic resin and adhered to the entire surface of one side of the reinforcing fiber sheet, pressed with a nip roll kept below the melting temperature of the (C) thermoplastic resin, and the impregnated reinforcing fiber sheet was cooled to obtain a fiber-reinforced resin intermediate. Next, a specified (B) thermosetting resin (described in each Example and Comparative Example; similar to Methods II and III) was applied using a knife coater to a resin basis weight of 100 g / m 2 After coating the resin on a release paper to produce a thermosetting resin film, the thermosetting resin film was placed on the surface opposite to the surface of the intermediate body impregnated with the thermoplastic resin (C), and the fiber-reinforced resin intermediate body was impregnated while being heated and pressurized by a heat roll to obtain a prepreg. At this time, the peak temperature of the tan δ curve of the prepreg was adjusted by the contact time between the fiber bundle passing through the heat roll and the roll temperature. The contact time between the fiber bundle and the roll was adjusted by the number of roll stages and the passing speed of the fiber bundle. The running direction of the reinforcing fiber sheet during impregnation is the longitudinal direction of the reinforcing fibers in the case of a prepreg in which the reinforcing fibers are arranged in one direction, and is the longitudinal direction of the fabric in the case of a prepreg made of a reinforcing fiber fabric.

[0069] [Method II] (B) Thermosetting resin is applied using a knife coater at a resin weight of 50 g / m 2 The resin film was coated on a release paper with (A) a thermosetting resin film having a basis weight of 193 g / m 2 The fiber-reinforced resin intermediate was obtained by impregnating the thermosetting resin into the reinforcing fiber sheet while heating and pressing the sheet using heat rolls. A film of thermoplastic resin (C) was placed on the surface of the fiber-reinforced resin intermediate, and the thermoplastic resin (C) was impregnated into the sheet while heating and pressing the sheet to obtain a prepreg. The peak temperature of the tan δ curve of the prepreg was adjusted by the contact time between the fiber bundle passing through the heat rolls and the roll temperature in the same manner as described above.

[0070] [Method III] (B) Thermosetting resin is applied using a knife coater at a resin weight of 50 g / m 2 The resin film was coated on a release paper with (A) a thermosetting resin film having a basis weight of 193 g / m 2 The prepreg was obtained by overlapping both sides of the reinforcing fiber sheet and impregnating the reinforcing fiber sheet with the thermosetting resin while heating and pressing the sheet using heat rolls. The peak temperature of the tan δ curve of the prepreg was adjusted by the contact time between the fiber bundle passing through the heat rolls and the roll temperature in the same manner as described above.

[0071] (3) Measurement of tan δ peak temperature by dynamic viscoelasticity measurement (DMA method) A sample of about 1g was taken from the prepreg, consisting of only the area where the (A) reinforcing fiber was impregnated with (B) thermosetting resin, and the peak temperature of the tan δ curve of this sample was determined by the DMA method using a dynamic viscoelasticity analyzer (ARES rheometer, manufactured by TA Instruments) in accordance with JIS C6481. The temperature corresponding to the peak in the tan δ=G" / G' curve, obtained from the ratio of the storage modulus G' and loss modulus G" of each prepreg, was evaluated. The temperature was measured at a heating rate of 5°C / min and a frequency f of 1 Hz.

[0072] (4) How to check the fibers at the interface A sample of 10 mm length x 10 mm width was taken from the prepreg, and the presence of (A) reinforcing fiber across the boundary between the resin region of (B) thermosetting resin and the resin region of (C) thermoplastic resin was confirmed by the following procedure. The samples were taken from 10 randomly selected locations, and each sample was ultrasonically cleaned with methyl alcohol for 30 minutes to remove the (C) thermoplastic resin. The obtained samples were observed with a scanning electron microscope (VK-9510: Keyence Corporation). When it was observed that one or more fibers were exposed on the surface of each of the 10 sample locations, it was determined that there was a reinforcing fiber (A) across the boundary between the (B) thermosetting resin and the (B) thermosetting resin.

[0073] (5) Drapability As shown in FIG. 3, the prepreg was cut into a width of 25 mm and a length of 300 mm to be used as a sample for evaluation. In the case of a prepreg in which the reinforcing fibers are arranged in one direction, the longitudinal direction of the fibers was set as the length direction of the sample, and in the case of a prepreg made of a reinforcing fiber woven fabric, the length of the woven fabric was set as the longitudinal direction of the sample. In a room environment (23°C), 100 mm from the end of the sample was fixed to the top surface of a horizontal test table with adhesive tape, and then further fixed with cellophane tape from above. The remaining 200 mm part was protruding into the air, and the sample was held so that it was horizontal. After removing the holding, the sample was allowed to hang down, and the angle at which the tip of the sample was bent under its own weight 5 minutes later was evaluated as drapeability. At this time, the lowest point of the tip of the sample bent under its own weight was set as point a, the base protruding into the air was set as point b, and the intersection point when the sample was stretched vertically from point a and horizontally from point b was set as point c, and the drape angle θ is expressed by the following formula. This measurement was performed at five points, and the arithmetic average value was taken as drapeability. Drape angle θ(°) = {tan -1 (lac / lbc)}·(180 / π) Here, lac is the distance between points a and c, and lbc is the distance between points b and c.

[0074] (6) Measurement of loss angle δ curve by dynamic viscoelasticity measurement method (DMA method) Only the area where the (B) thermosetting resin was impregnated into the (A) reinforcing fibers was taken from the prepreg and used for the measurement. However, if the thickness of the sample was less than 1 mm, the samples were laminated to a thickness of about 1 mm. Also, for uniaxial materials, the fiber direction of the (A) reinforcing fibers was defined as 0°, and the direction perpendicular to the fibers was defined as 90°, so that the [0° / 90°] S The loss angle δ (=tan -1The thermal expansion coefficient (G") / (G') was measured. The temperature was raised from 30°C to 80°C at a rate of 5°C / min, and then the isothermal measurement was started at 80°C. The measurement frequency was 10 Hz. Incidentally, 80°C is a mold temperature that is often used in integral molding.

[0075] (7) Thickness of the prepreg, thermoplastic resin region, and thermosetting resin region A sample of 20 mm length x 25 mm width was taken from the prepreg, and the thickness of each part was measured as follows. The cross section of the sample was magnified 200 times with a laser microscope (VK-9510: manufactured by Keyence Corporation), and images were taken of 10 randomly selected locations that did not overlap with each other (for example, as observed in FIG. 2). In each image taken, 10 measurement positions (vertical base line for thickness measurement, 10) were set at equal intervals, and the total thickness of the prepreg and the thickness of the thermoplastic resin region were measured. The average values ​​of the measurement data for a total of 100 points were taken as the representative prepreg thickness T and the thickness of the thermoplastic resin region Tp, and the difference was taken as the thickness of the thermosetting resin region Ts.

[0076] (8) Tensile strength perpendicular to the grain For the prepreg in which the reinforcing fibers are aligned in one direction, a sample of 50 mm wide and 150 mm long was cut out with the direction perpendicular to the orientation of the reinforcing fibers as the longitudinal direction, to prepare an evaluation sample. The evaluation sample was set in a tabletop precision universal testing machine (Autograph AGS: manufactured by Shimadzu Corporation) so that the distance between the gripping jigs was 100 mm, and a tensile test was performed at room temperature (23°C) at a speed of 100 mm / min. The maximum load until the sample broke was Pmax, and the horizontal cross-sectional area perpendicular to the longitudinal direction of the sample was A, and the tensile strength (MPa) perpendicular to the fibers was calculated from the following formula.

[0077] Tensile strength perpendicular to the grain (MPa) = Pmax / A.

[0078] (9) Ease of use From the viewpoint of the sticking property of the prepreg of the present invention to work gloves when handled in a room temperature environment (23° C.), the ease of handling was relatively evaluated on the following four-point scale. ◎: When the prepreg is picked up, it does not stick to work gloves and resin does not adhere to it. Good: When the prepreg is picked up, it does not stick to the work gloves, but a small amount of resin adheres to them. △: When the prepreg was picked up, it stuck to the work gloves, but the orientation of the (A) reinforcing fibers contained in the prepreg was not disturbed. ×: When the prepreg was picked up, it stuck to the work gloves, and the orientation of the (A) reinforcing fibers contained in the prepreg was disturbed.

[0079] (10) Molding of the molded body The prepreg was placed on a mold preheated to 80°C, with the surface without the (C) thermoplastic resin in contact with the injection molding mold surface, and held in that state until it was completely cured, yielding a molded product conforming to the shape of the mold.

[0080] (11) Molding of an integrally molded body The injection molding and press molding methods are respectively shown below.

[0081] [Integration through injection molding] The prepreg (C) was inserted into a mold preheated to 80°C so that the surface without thermoplastic resin was in contact with the injection molding mold surface, and (D) the injection molding material was injected and filled into the mold to obtain an integrated molded body reinforced and stiffened by the prepreg. Here, (D) the injection molding material was heated and melted in a heating cylinder to its melting point +30°C, and injection molded at a screw rotation speed of 60 rpm, injection speed of 90 mm / sec, injection pressure of 200 MPa, and back pressure of 0.5 MPa.

[0082] The injection mold used for the integrated molding had a plane of 300 mm length x 300 mm width, and a curved surface of a cylinder of 225 mm radius x 280 mm height with an arc length of 302 mm.

[0083] [Integration through press molding] After overlapping the surface of the prepreg containing the (C) thermoplastic resin and the (E) thermoplastic plate, they were placed so that the surface not containing the (C) thermoplastic resin was in contact with the flat mold surface preheated to 80°C, and pressure was applied with a press, and the temperature was raised to the melting point of the (E) thermoplastic plate + 30°C, after which it was held for 1 minute to obtain an integrated molded body. The evaluation was carried out under two conditions of pressure applied with the press: low pressure (0.5 MPa) and high pressure (5.0 MPa).

[0084] (12) Adhesion to the mold During molding of the above-mentioned integrally molded product, the prepreg was placed in a mold for injection molding, and its adhesion to the mold was relatively evaluated on the following four-point scale. ◎: The prepreg adhered to the mold in less than 3 seconds after being pressed against the mold, and no misalignment occurred on the mold. Good: The prepreg adhered to the mold within 3 to 10 seconds after being pressed against the mold, and no misalignment occurred on the mold in any of the five molding cycles. △: The prepreg adhered to the mold within 3 to 10 seconds after being pressed against the mold, but the adhesion was unstable. No misalignment on the mold occurred in 2 to 4 moldings out of 5 molding runs. ×: The prepreg was not easily adhered to the mold even after 10 seconds or more had passed since it was pressed against the mold, and no misalignment on the mold occurred in 0 to 1 of 5 molding cycles.

[0085] (13) Ability to mold onto curved mold surfaces During molding of the above-mentioned integrated molded product, the prepreg was placed in a mold for injection molding, and its shapeability onto the curved surface of the mold was relatively evaluated on the following four-point scale. ◎: Flexibility was exhibited within 3 seconds after the prepreg was pressed against the mold, and the prepreg was able to be shaped to fit the curved mold surface. ◯: Flexibility was exhibited 3 to 10 seconds after the prepreg was pressed against the mold, and the prepreg was able to be shaped along the curved mold surface in all five molding cycles. △: Flexibility was exhibited 3 to 10 seconds after the prepreg was pressed against the mold, but the flexibility was unstable, and the prepreg was able to be shaped to fit the curved mold surface in 2 to 4 out of 5 molding cycles. ×: The prepreg had low flexibility even after 10 seconds or more had passed since it was pressed against the mold, so that it was possible to mold the prepreg along the curved mold surface in 0 to 1 out of 5 molding attempts.

[0086] The moldability of the prepreg of the present invention is expressed by relatively evaluating both the adhesion to the mold and the moldability onto the curved surface of the mold.

[0087] (14) Appearance evaluation of the integrally molded body After molding the above-mentioned integrated molded body, the prepreg was evaluated on the following four-point scale based on the degree of shifting of the prepreg toward the inside of the molded product, the degree of shifting toward the side of the molded product, the maintenance of fiber straightness, and the presence or absence of gaps inside the prepreg. ◎: All are good 〇: Inferior in any one point △: Inferior in any two points ×: Inferior in any of three or more points.

[0088] (15) Bond strength evaluation The procedure for preparing the sample for evaluating the bonding strength and the evaluation method are described below.

[0089] The (B) thermosetting resin used in the corresponding Examples or Comparative Examples was used, and a resin weight of 50 g / m was applied using a knife coater. 2 The resin film was coated on a release paper with a thermosetting resin film. 2The reinforcing fiber sheet was laminated on both sides of the sheet and heated using heat rolls to impregnate the reinforcing fiber with a thermosetting resin while heating and pressurizing it, and then cut into a size of 200 mm wide x 150 mm long to obtain a prepreg (for convenience, referred to as a lower layer prepreg). The peak temperature of the tan δ curve of the lower layer prepreg was adjusted to be less than 30°C by adjusting the contact time between the fiber bundle passing through the heat rolls and the roll temperature.

[0090] Next, in the case of (A) a prepreg in which the reinforcing fibers are arranged in one direction, one prepreg produced in the Example or Comparative Example was cut to a size of 200 mm wide x 150 mm long, and this was laminated on top of the seven lower layer prepregs described above in a [0° / 90°]2S (the symbol S indicates a mirror image) arrangement in which the fiber direction of the (A) reinforcing fibers is defined as 0° and the direction perpendicular to the fibers is defined as 90°, so that the surface containing the (C) thermoplastic resin appears as the surface facing outward, thereby obtaining a laminate.

[0091] Furthermore, when the (A) reinforcing fibers consisted of a plain weave fabric, one prepreg prepared in the Example or Comparative Example was cut to a size of 200 mm in width and 150 mm in length, and laminated to seven of the lower layer prepregs described above such that the surface containing the (C) thermoplastic resin was exposed as the outer surface, thereby obtaining a laminate.

[0092] In addition, when the sample did not have a surface containing (C) thermoplastic resin, the direction in which the (A) reinforcing fibers were oriented was set to 0°, and the direction perpendicular to that direction was set to 90°, and the sample was laminated with no distinction between the front and back surfaces as [0° / 90°]2S (the symbol S indicates a mirror image).

[0093] In the evaluation of the bonding strength of the integrally molded body by injection molding, the laminate was placed in an injection mold for preparing a sample for evaluating the bonding strength shown in FIG. 5 so that the prepreg prepared in the Examples or Comparative Examples was on the opposite side to the mold side. Next, an injection molding machine (J150EII-P: manufactured by JSW) was used to introduce the injection molding material (described in each Example and Comparative Example) into the mold, and an integrally molded body for evaluating the bonding strength was prepared in which the injection molding material and the laminate were bonded in an area of ​​200 mm wide x 12.5 mm long. The integrally molded body was then placed in an oven, and the (B) thermosetting resin was completely cured by heat treatment. Here, the (D) injection molding material was heated and melted to the melting point +30°C in a heating cylinder, and injection molded at a screw rotation speed of 60 rpm, an injection speed of 90 mm / sec, an injection pressure of 200 MPa, and a back pressure of 0.5 MPa. The obtained integrated molded body for evaluating the bonding strength was cut to a size of 180 mm in width and 172.5 mm in length, with the fiber direction on the surface being the longitudinal direction of the sample, and then dried in a vacuum oven for 24 hours. The sample was tab-bonded in accordance with ISO4587:1995 (JIS K6850(1994)) and cut to a width of 25 mm to obtain a sample for evaluating the bonding strength.

[0094] In the evaluation of the bonding of the integrally molded body by press molding, the laminate was placed in a press molding die for preparing a sample for evaluating the bonding strength, which has the same uneven shape as shown in FIG. 5, so that the prepreg prepared in the Example or Comparative Example was on the opposite side to the side of the die. Next, a thermoplastic plate (described in each Example and Comparative Example) was prepared by adjusting the thickness by heating and press molding at a melting point +30°C so that it could be placed in the press molding die, and then cut to a width of 200 mm x length of 150 mm. The thermoplastic plate was placed in the press molding die so as to be bonded to the laminate in an area of ​​width 200 mm x length 12.5 mm, and an integrally molded body for evaluating the bonding strength was prepared. Here, the die temperature was preheated to 80°C, and after the laminate and the thermoplastic plate were placed in the die, the temperature was raised to the melting point of the thermoplastic plate +30°C, and then heating and press molding was performed under two conditions, a low pressure (0.5 MPa) and a high pressure (5.0 MPa). The obtained integrated molded body for evaluating the bonding strength was cut to a size of 180 mm in width and 172.5 mm in length, with the fiber direction on the surface being the longitudinal direction of the sample, and then dried in a vacuum oven for 24 hours. The sample was tab-bonded in accordance with ISO4587:1995 (JIS K6850(1994)) and cut to a width of 25 mm to obtain a sample for evaluating the bonding strength.

[0095] The obtained samples for evaluation of bonding strength were subjected to measurement of tensile shear bonding strength in a room temperature environment (23° C.) based on ISO4587:1995 (JIS K6850 (1994)), and the bonding strength was evaluated.

[0096] In this evaluation, (A) in the case of prepregs in which the reinforcing fibers are arranged in one direction, the prepregs of the Examples and Comparative Examples were prepared so that the reinforcing fibers were aligned in the longitudinal direction, and in the case of prepregs made of woven reinforcing fiber fabrics, the prepregs of the Examples and Comparative Examples were prepared so that the reinforcing fibers were aligned in the longitudinal direction of the fabric.

[0097] (16) Coefficient of variation The variation in bonding strength is represented by the coefficient of variation. The bonding strength evaluation was performed five times, the standard deviation and average value were calculated, and the coefficient of variation was calculated using the following formula. Coefficient of variation (%) = standard deviation / average value x 100 Comparative Example 1 A prepreg having a peak temperature of the tan δ curve shown in Table 1 was produced by the production method III using A-1 as (A) reinforcing fiber and B-1 as (B) thermosetting resin. The prepreg was then inserted into an injection molding die, and insert injection molding was performed using D-1 as the injection molding material. Separately, a prepreg produced by the production method III was inserted into a press molding die, and press molding was performed using E-1 as the thermoplastic plate material. The characteristics and moldability of the prepreg, and the evaluation results of the integrally molded body obtained after injection molding and the integrally molded body after press molding are summarized in Table 1.

[0098] The moldability was good, but the bonding strength of the integrally molded bodies obtained was extremely low.

[0099] Example 1 A prepreg having a peak temperature of the tan δ curve shown in Table 1 was produced by the production method II using A-1 as (A) reinforcing fiber, B-1 as (B) thermosetting resin, and C-4 as (C) thermoplastic resin. The prepreg was then inserted into an injection molding die, and insert injection molding was performed using D-2 as an injection molding material. Separately, a prepreg produced by the production method II described above was inserted into a press molding die, and press molding was performed using E-2 as a thermoplastic plate material. The characteristics and moldability of the prepreg, and the evaluation results of the integrally molded body obtained after injection molding and the integrally molded body after press molding are summarized in Table 1.

[0100] The moldability was good, and all of the molded articles exhibited satisfactory bonding strength as integrally molded bodies.

[0101] (Comparative Example 2, Comparative Example 4, Example 2, Examples 6 to 9) Using the (A) reinforcing fiber, (B) thermosetting resin, and (C) thermoplastic resin shown in Table 1, a prepreg having a peak temperature of the tan δ curve shown in Table 1 was produced by the production method I. Thereafter, the prepreg was inserted into an injection molding die, and insert injection molding was performed using D-1 as the injection molding material. Separately, a prepreg produced by the production method I described above was inserted into a press molding die, and press molding was performed using E-1 as the thermoplastic plate material. The characteristics and moldability of the prepreg, and the evaluation results of the integrally molded body obtained after injection molding and the integrally molded body after press molding are summarized in Table 1.

[0102] In Comparative Example 2, the fiber straightness of the integrally molded body was greatly disturbed, and in Comparative Example 4, the prepreg moved in the mold and could not be placed at the target location. On the other hand, Examples 6 to 9 had high bonding strength, and in particular, Examples 7 and 8 had excellent moldability, as expressed by adhesion to the mold and moldability on the mold curved surface, while also exhibiting extremely high bonding strength. In addition, Example 9 had excellent handleability in a room temperature environment (23°C), and although its moldability was inferior to Examples 6 to 8, there was no disturbance in the fiber straightness even in the integrally molded body obtained by high-pressure press molding, and the appearance was better than Examples 7 and 8, which were press molded under the same conditions.

[0103] Comparative Example 3 A prepreg was produced by the production method I using A-2 as (A) reinforcing fiber, B-1 as (B) thermosetting resin, and C-2 as (C) thermoplastic resin. The prepreg was then inserted into an injection molding die, and insert injection molding was carried out using D-1 as the injection molding material. Separately, a prepreg produced by the production method I described above was inserted into a press molding die, and press molding was carried out using E-1 as a thermoplastic plate material. The characteristics and moldability of the prepreg, and the evaluation results of the integrally molded body obtained after injection molding and the integrally molded body after press molding are summarized in Table 1.

[0104] In all of the integrated molded bodies, the fibers were disordered from the ends of the arranged prepregs.

[0105] (Examples 3 to 4) Using the (A) reinforcing fiber, (B) thermosetting resin, and (C) thermoplastic resin shown in Table 1, a prepreg having a peak temperature of the tan δ curve shown in Table 1 was produced by the production method I. Thereafter, the prepreg was inserted into an injection molding die, and insert injection molding was performed using D-1 as the injection molding material. Separately, a prepreg produced by the production method I described above was inserted into a press molding die, and press molding was performed using E-1 as the thermoplastic plate material. The characteristics and moldability of the prepreg, and the evaluation results of the integrally molded body obtained after injection molding and the integrally molded body after press molding are summarized in Table 1.

[0106] In Example 3, the prepreg had high rigidity, but had good adhesion to the mold, and it was possible to mold the prepreg into an integrated body. In Examples 3 and 4, the fiber straightness of the injection-molded integrated body was slightly impaired in some places, but excellent bonding strength was achieved. On the other hand, the fiber straightness of the integrated body molded by high-pressure press molding was greatly disturbed and spread due to the resin flow, and the shape could not be maintained.

[0107] Example 5 A prepreg having a peak temperature of the tan δ curve shown in Table 1 was produced by the production method I using A-2 as (A) reinforcing fiber, B-1 as (B) thermosetting resin, and C-2 as (C) thermoplastic resin. The prepreg was then inserted into an injection molding die, and insert injection molding was performed using D-1 as the injection molding material. Separately, a prepreg produced by the production method I described above was inserted into a press molding die, and press molding was performed using E-1 as the thermoplastic plate material. The characteristics and moldability of the prepreg, and the evaluation results of the integrally molded body obtained after injection molding and the integrally molded body after press molding are summarized in Table 1.

[0108] The injection molded integral product had an excellent appearance in that the fiber straightness was better maintained than in Comparative Example 3, but the appearance of the integrally molded product that had been subjected to high-pressure press molding showed that the fiber straightness was significantly disrupted from the ends of the prepreg. (Examples 10 to 12) A prepreg was produced by adjusting the peak temperature of the tan δ curve shown in Table 2 using A-1 as (A) reinforcing fiber, B-1 as (B) thermosetting resin, and C-4 as (C) thermoplastic resin, according to the production method II. The prepreg was then inserted into an injection molding die, and insert injection molding was carried out using D-2 as the injection molding material. Separately, a prepreg produced by the production method II described above was inserted into a press molding die, and press molding was carried out using E-2 as the thermoplastic plate material. The characteristics and moldability of the prepreg, and the evaluation results of the integrally molded body obtained after injection molding and the integrally molded body after press molding are summarized in Table 2.

[0109] In all of the integrally molded bodies, the moldability expressed by the adhesion to the mold and the moldability to the mold curved surface was good, and the appearance was good. In particular, Example 11 exhibited extremely high bonding strength while exhibiting good moldability and appearance. On the other hand, in the high pressure press molding, the appearance of Example 12 was better than that of Example 11.

[0110] (Examples 13 to 19) A prepreg having a peak temperature of the tan δ curve shown in Table 2 was produced by the production method I using the (A) reinforcing fiber, (B) thermosetting resin, and (C) thermoplastic resin shown in Table 2. Thereafter, the prepreg was inserted into an injection molding die, and insert injection molding was performed using the injection molding material shown in Table 2. Separately, a prepreg produced by the production method I described above was inserted into a press molding die, and press molding was performed using the thermoplastic plate material shown in Table 2. The characteristics and moldability of the prepreg, and the evaluation results of the integrally molded body obtained after injection molding and the integrally molded body after press molding are summarized in Table 2.

[0111] All prepregs had good handleability at room temperature (23°C), and particularly Examples 15-16 and 18-19 had even better handleability. All integrally molded bodies achieved both moldability and appearance, and demonstrated high bonding strength. In high-pressure press molding, Examples 13-14 and 17 showed significant disruption of fiber straightness at the prepreg ends. On the other hand, Examples 16 and 19, which were press molded under the same conditions, had extremely good appearance and were excellent in shape retention.

[0112] (Examples 20 to 25) Using the (A) reinforcing fiber, (B) thermosetting resin, and (C) thermoplastic resin shown in Table 3, a prepreg having a peak temperature of the tan δ curve shown in Table 3 was produced by the production method I. Then, the prepreg was inserted into an injection mold, and insert injection molding was performed using D-1 as the injection molding material. Separately, a prepreg produced by the production method I described above was inserted into a press molding mold, and press molding was performed using E-1 as the thermoplastic plate material. The characteristics and moldability of the prepreg, and the evaluation results of the integrally molded body obtained after injection molding and the integrally molded body after press molding are summarized in Table 3.

[0113] The integrally molded bodies of Examples 20 to 24 all achieved both moldability and appearance, and exhibited high bonding strength. In particular, the bonding strength of Examples 20 and 22 to 24 was even higher. Furthermore, the variation in bonding strength of the integrally molded bodies of Examples 21 and 22 was extremely low. The integrally molded body of Example 25 was inferior to Examples 20 and 22 to 24, but had a satisfactory bonding strength as an integrally molded body.

[0114] (Examples 26 to 30) A prepreg having a peak temperature of the tan δ curve shown in Table 3 was produced using (A) reinforcing fiber, (B) thermosetting resin, (C) thermoplastic resin, and production method shown in Table 3. The prepreg was then inserted into an injection mold, and insert injection molding was performed using the injection molding material shown in Table 3. Separately, a prepreg produced by the above-mentioned production method I was inserted into a press molding mold, and press molding was performed using the thermoplastic plate material shown in Table 3. The characteristics and moldability of the prepreg, and the evaluation results of the integrally molded body obtained after injection molding and the integrally molded body after press molding are summarized in Table 3.

[0115] In all of the integrally molded bodies using different combinations of materials, it was possible to achieve both moldability and appearance, and a higher bonding strength was achieved.

[0116] (summary) Example 1 had superior bonding strength of the integrally molded body compared to Comparative Example 1. This is because the surface of the prepreg in Example 1 was covered with the thermoplastic resin (C) having thermal welding properties, which enabled it to be integrated with the injected material. On the other hand, the prepreg in Comparative Example 1, which was not covered with the thermoplastic resin (C), appeared to be integrated with the injected material, but had such low bonding strength that it could be easily peeled off by hand.

[0117] In comparison with Comparative Examples 2 and 4 and Examples 6 to 19, it was confirmed that the peak temperature of the tan δ curve was 30°C or more and 100°C or less, which resulted in good adhesion and shaping properties on the injection molding die, and excellent moldability. This is thought to be due to the moderate adhesion and flexibility exhibited on the die, and this effect resulted in an integrally molded product with excellent appearance and bonding strength. In particular, Examples 7, 8, 15, and 18 were excellent in the balance of moldability and the appearance of the integrally molded product, and it was thought that the peak temperature of the tan δ curve was about 60°C or more and 80°C or less, which allowed good adhesion and flexibility to be obtained by heating from the die surface while maintaining the straightness of the (A) reinforcing fiber.

[0118] The results of Comparative Examples 2 and 3 were almost the same. This was thought to be because the peak temperature of the tan δ curve was less than 30°C, similar to that of the prepreg in which the (A) reinforcing fibers of the prepreg were woven and arranged in one direction, and the fiber linearity of the prepreg end was impaired by the injection pressure during insert injection molding. This tendency was also confirmed by comparing Examples 4 and 5.

[0119] The appearance of the integrally molded product of Example 5 was superior to that of Comparative Example 3. This was believed to be because, even when (A) the reinforcing fibers were woven, (B) the thermosetting resin had a specific peak temperature of the tan δ curve, which made it easier to maintain the straightness of the fibers.

[0120] By comparing Examples 6, 7, and 9 with Examples 10 to 12, it was confirmed that even when the manufacturing method of the prepreg was different, the same degree of moldability and appearance of the integrally molded product could be obtained by adjusting the peak temperature of the tan δ curve.

[0121] Compared with Example 1, Example 7 showed even better bonding strength after integral molding, and it was believed that the (A) reinforcing fibers were able to exert a strong bonding force by spanning the boundary surface between the (B) thermosetting resin and the (C) thermoplastic resin.

[0122] Example 2 had poorer moldability than Example 7, which was believed to be due to the low flexibility and rigidity of the prepreg. Furthermore, Example 3 also had poorer moldability than Example 7, which was believed to be due to the (C) thermoplastic resin being thick and low in flexibility. Although Example 4 had excellent adhesion to the curved surface of the mold and excellent formability, the appearance of the integrally molded product was slightly inferior to that of Example 7. This was thought to be because the tensile strength perpendicular to the fibers of the prepreg was low, and therefore the straightness of the fibers was impaired by the injection pressure during hot and cold molding.

[0123] By comparing Examples 6 to 9 with Examples 13 to 16 and Examples 17 to 19, it was confirmed that the same moldability and the appearance of the integral molding can be obtained by adjusting the peak temperature of the tan δ curve for any prepreg using different materials. It was also confirmed that a prepreg having a peak temperature of tan δ exceeding 60°C has better handleability in a room temperature environment (23°C). When the peak temperature of the tan δ curve exceeds 80°C, the moldability represented by the adhesion to the mold and the moldability to the mold curved surface is inferior, but it was suggested that there is little disturbance in the straightness of the fibers even during high-pressure press molding, and that the shape retention is excellent.

[0124] The bonding strength of Examples 20 to 25 was further improved compared to Examples 6 to 9. That is, it is considered that the compound present on the surface of the (A) reinforcing fiber contributes to exhibiting a higher affinity with the (B) thermosetting resin and the (C) thermoplastic resin, and therefore a high bonding strength was exhibited at the interface between the (B) thermosetting resin and the (C) thermoplastic resin, which are straddled by the (A) reinforcing fiber. Also, the bonding strength of the integrally molded articles of Examples 20 and 22 to 24 was much higher, and the surface free energy of the (A) reinforcing fiber was 20 to 40 mJ / m 2 It has been found that it is preferable that

[0125] By comparing Examples 20 to 25 with Examples 26 to 30, it was confirmed that even when the (A) reinforcing fibers, (B) thermosetting resins, and (C) thermoplastic resins are different, the (A) reinforcing fibers exhibit a higher affinity with the (B) thermosetting resin and the (C) thermoplastic resin via the compounds present on the surface of the (A) reinforcing fibers, and high bonding strength can be obtained.

[0126] [Table 1]

[0127] [Table 2]

[0128] [Table 3] [Industrial Applicability]

[0129] The integrally molded article of the present invention is preferably used for computer applications such as aircraft structural members, wind turbine blades, automobile exterior panels and sheets, IC trays and notebook computer housings, and sports applications such as golf shafts and tennis rackets. [Explanation of symbols]

[0130] 1: Prepreg 2: (A) Reinforced fiber 3:(B) Thermosetting resin 4:(C)Thermoplastic resin 5: (A) Reinforced fiber layer impregnated with (B) thermosetting resin 6: (A) Reinforced fiber 7: (B) Resin region containing thermosetting resin 8: (C) Resin region containing thermoplastic resin 9: Boundary 10: Vertical baseline for thickness measurement 11: Prepreg 12: Test stand 13: Point a 14: Point b 15: Point c 16:Drape angle(°) 17: Area with gentle slope and no undulations 18: Peak position 19: Loss angle δ curve (peaked, shape 1) 20: Loss angle δ curve (with peak, shape 2) 21: Loss angle δ curve (no peak) 22: Laminate 23: Mold (movable side) 24: Mold (fixed side) 25: Injection molding machine 26: Injection molding material 27: Sample for evaluating bonding strength

Claims

1. A prepreg comprising (A) reinforcing fibers, (B) a thermosetting resin, and (C) a thermoplastic resin, wherein the (B) thermosetting resin is impregnated into the (A) reinforcing fibers, and the (C) thermoplastic resin is present on at least a portion of the surface of the prepreg, and (B) The thermosetting resin has a peak at 30°C or higher and 100°C or lower in a loss tangent tanδ curve measured by a dynamic viscoelasticity measurement method (DMA method), and A prepreg characterized by having (A) reinforcing fibers present across the boundary surface between (B) a resin region containing a thermosetting resin and (C) a resin region containing a thermoplastic resin.

2. 2. The prepreg according to claim 1, which has a drape property of 3° or more.

3. 3. The prepreg according to claim 1 or 2, wherein in a region where the (A) reinforcing fiber is impregnated with the (B) thermosetting resin, in a loss angle δ curve determined by dynamic viscoelasticity measurement (DMA method), the loss angle δ curve has a point showing a maximum value, and also has a point on the shorter-time side of the point showing the maximum value where the loss angle δ is 5° or more smaller than the maximum value.

4. 3. The prepreg according to claim 1 or 2, wherein in a region where the reinforcing fibers (A) are impregnated with the thermosetting resin (B), a loss angle δ curve obtained by dynamic viscoelasticity measurement (DMA) does not have a point showing a maximum value, or even if it has a maximum value, does not have a point on the shorter time side of the point showing the maximum value where the loss angle δ is 5° or more smaller than the maximum value.

5. 5. The prepreg according to claim 1, wherein the prepreg has an average thickness of 50 μm or more and 400 μm or less, and when the average thickness is taken as 100%, the average thickness of the resin region containing the thermoplastic resin (C) is 2% or more and 55% or less.

6. (A) As a reinforcing fiber, a surface free energy measured by the Wilhelmy method is 10 to 50 mJ / m 2 The prepreg according to any one of claims 1 to 5, which is formed using reinforcing fibers represented by the formula:

7. The prepreg according to any one of claims 1 to 6, wherein (A) the reinforcing fibers are arranged in one direction.

8. (A) The prepreg according to claim 7, wherein the tensile strength in a direction perpendicular to the arrangement direction of the reinforcing fibers and parallel to the sheet surface is 0.3 MPa or more.

9. A molded article obtained by using the prepreg according to any one of claims 1 to 8 and heat-curing (B) a thermosetting resin.

10. A molded article in which a thermoplastic resin is integrated by injection molding or by press molding onto the surface of the prepreg according to any one of claims 1 to 8 on the side where the thermoplastic resin (C) is present.

Citation Information

Patent Citations

  • Prepreg sheet of carbon fiber reinforced composite material

    JP1992004107A

  • Prepreg and fiber-reinforced composite material

    JP1996259713A

  • Carbon fiber reinforced resin molded product and its manufacture

    JP1998138354A

  • Thermosetting resin composition, prepreg and fiber-reinforced composite material

    JP2004315743A

  • Heat-conductive forming and method of producing the same

    JP2006049878A